Investigation of Wear Behaviour of Al6061 reinforcement with TiC and MoS2 - Rajesh, S.; Velmurugan, C. (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Metal matrix composite (MMC) focuses primarily on improved specific strength, high temperature and wear resistance application. Aluminum matrix reinforced with titanium carbide and molybdenum disulfide has good potential and also self-lubrication. The main challenge is to produce this composite in a cost effective way to meet the above requirements. In this study Alâ€“TiC-MoS2 castings with different volume fraction of TiC and MoS2 were produced in an argon atmosphere by an enhanced stir casting method. Hardness of the composite has increased with higher % of TiC addition. At that same time self-lubrication of composite has occur in the effort of MoS2. Dry sliding wear behavior of AMC was analyses with the help of a pin on disc wear and friction monitor. The present analyses reveal the improved hardnessÂ  as well as wear resistance.